A Review of Intraocular Biomolecules in Retinal Vein Occlusion: Toward Potential Biomarkers for Companion Diagnostics - Wang, Bingjie; Zhang, Xiao; Chen, Huan; Koh, Adrian; Zhao, Chan; Chen, Youxin (Frontiers in Pharmacology, 2022)
Retinal vein occlusion (RVO) is one of the most common retinal vascular diseases. The pathogenesis of RVO is multifactorial and involves a complex interplay among a variety of vascular and inflammatory mediators, many cytokines, chemokines, growth factors and cell adhesion molecules have been reported to be implicated. Treatments for RVO are directed at management of underlying risk factors and vision-threatening complications including macula edema (ME) and neovascularization. Intravitreal anti-VEGF agents are currently considered as the first-line treatment for ME secondary to RVO (RVO-ME), but a substantial proportion of patients responded insufficiently to anti-VEGF agents. Since RVO-ME refractory to anti-VEGF agents generally responds to corticosteroids and its visual outcome is negatively correlated to disease duration, prediction of treatment response at baseline in RVO-ME may significantly improve both cost-effectiveness and visual prognosis. Several bioactive molecules in the aqueous humor were found to be associated with disease status in RVO. This review aims to present a comprehensive review of intraocular biomolecules reported in RVO, including VEGF, IL-6, IL-8, MCP-1, sICAM-1, IL-12, IL-13, sVEGFR-1, sVEGFR-2, PDGF-AA, etc.. highlighting their association with disease severity and/or phenotype, and their potential roles in prognostic prediction and treatment selection. Some of these molecules may serve as biomarkers for aqueous humor based companion diagnostics for the treatment of RVO in the future.